Strategies for Sustainable Use of Seagrass Ecosystem in Coastal Area around Borgo Village, Belang District, Southeast Minahasa Regency - Losung, Agung; Paruntu, Carolus Paulus; Wagey, Billy Theodorus; Roeroe, Kakaskasen Andreas; Losung, Fitje; Sambali, Hariyani (Sam Ratulangi University, 2023)
The objective of this research is to formulate strategies for the sustainable use of the seagrass ecosystem in the coastal area around Borgo Village, Belang District, Southeast Minahasa Regency as a public policy recommendation that can be given to the local regional government. The research method is a survey method with an interview technique using a questionnaire addressed to the heads of relevant agencies as resource persons. The formulation of priority strategies is analyzed through the following stages: 1) Establishing the vision, mission, and values ​of the organization, 3) Analysis of the strategic environment, 4) Analysis of the final conclusions of internal and external factors, 5) SWOT analysis matrix, and (6) Determining critical success factors through strategic choice analysis. The research results obtained 6 priority strategies, namely: 1) Make academic papers as a data base on: a) coastal and marine resource profiles, b) social, economic and cultural data, and c) legal data and community institutions in the region the coast of Borgo Village and its surroundings; 2) Carry out technical guidance, counseling and outreach to the coastal communities of Borgo Village and its surroundings; 3) Provide guidance to fishermen and input to the government of Southeast Minahasa Regency so that the seagrass ecosystem area on the coast of Borgo Village and its surroundings is not used as a boat mooring location and a location for disposal of marine debris or household waste; 4) Make standard operational procedures on boat moorings, disposal of marine debris, household waste, and marine conservation techniques for the coastal communities of Borgo Village and its surroundings; 5) Empowerment of fishermen or coastal communities in Borgo Village and its surroundings in order to carry out the task of supervising and monitoring coastal and marine resources, as well as fostering the quality and processing of fishery products; and 6) Make a spatial plan for the Minapolitan area in the coastal area of Belang Regency based on Regional Regulation Number 1 of 2017 of North Sulawesi Province. Keywords: Borgo Village, seagrass ecosystem, sustainable use, priority strategy Abstrak Tujuan penelitian adalah merumuskan strategi pemanfaatan berkelanjutan ekosistem padang lamun di pesisir sekitar Desa Borgo, Kecamatan Belang, Kabupaten Minahasa Tenggara sebagai rekomendasi kebijakan publik untuk diberikan kepada Pemerintah Daerah setempat. Metode penelitian adalah metode survei dengan teknik wawancara menggunakan kuesioner ditujukan kepada pimpinan instansi terkait sebagai narasumber. Perumusan strategi prioritas dianalisis melalui tahapan: 1) Menetapkan visi, misi dan nilai organisasi, 3) Analisis lingkungan strategis, 4) Analisis kesimpulan akhir faktor internal dan eksternal, 5) Matriks analisis SWOT, dan (6) Menetapkan faktor-faktor kunci keberhasilan melalui analisis pilihan strategis. Hasil penelitian diperoleh 6 strategi prioritas, yaitu: 1) Membuat naskah akademik sebagai database tentang: a) profil sumber daya pesisir dan laut, b) data sosial, ekonomi dan budaya, dan c) data hukum dan kelembagaan masyarakat di pesisir Desa Borgo dan sekitarnya; 2) Melaksanakan bimbingan teknis, penyuluhan dan sosialisasi kepada masyarakat pesisir Desa Borgo dan sekitarnya; 3) Memberikan pembinaan kepada nelayan dan masukan kepada Pemerintah Kab. Minahasa Tenggara, agar di area ekosistim lamun pesisir Desa Borgo dan sekitarnya tidak dijadikan lokasi penambatan perahu dan tempat pembuangan sampah laut atau limbah rumah tangga; 4) Membuat SOP tentang tambatan perahu, tempat pembuangan sampah laut dan limbah rumah tangga, dan teknis konservasi laut kepada masyarakat pesisir Desa Borgo dan sekitarnya; 5) Memberdayakan nelayan atau masyarakat pesisir Desa Borgo dan sekitarnya dalam rangka melaksanakan tugas pengawasan dan pemantauan sumber daya pesisir dan laut, serta pembinaan mutu dan pengolahan hasil perikanan; dan 6) Membuat perencanaan penataan ruang di kawasan Minapolitan wilayah pesisir Belang berdasarkan Perda No. 1 Tahun 2017 Prov. SULUT. Kata kunci: Desa Borgo, ekosistim lamun, pemanfaatan berkelanjutan, strategi prioritas